1999
DOI: 10.1002/(sici)1097-0274(199903)35:3<246::aid-ajim4>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Latency analysis in epidemiologic studies of occupational exposures: Application to the Colorado plateau uranium miners cohort

Abstract: Background Latency effects are an important factor in assessing the public health implications of an occupational or environmental exposure. Usually, however, latency results as described in the literature are insufficient to answer public health related questions. Alternative approaches to the analysis of latency effects are warranted. Methods A general statistical framework for modeling latency effects is described. We then propose bilinear and exponential decay latency models for analyzing latency effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…To illustrate an extension of the proposed approach for background stratified Poisson regression analysis to an analysis in which a time-varying weight function is used to describe the modification of a cumulative dose–response association by time-since-exposure, we use data from a study of underground uranium miners (Hornung and Meinhardt 1987; Langholz et al 1999). The Colorado Plateau cohort that we examined includes 2,704 white men employed in underground uranium mining operations between 1 January 1950 and 31 December 1960.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate an extension of the proposed approach for background stratified Poisson regression analysis to an analysis in which a time-varying weight function is used to describe the modification of a cumulative dose–response association by time-since-exposure, we use data from a study of underground uranium miners (Hornung and Meinhardt 1987; Langholz et al 1999). The Colorado Plateau cohort that we examined includes 2,704 white men employed in underground uranium mining operations between 1 January 1950 and 31 December 1960.…”
Section: Resultsmentioning
confidence: 99%
“…One important example arises when modeling latency effects for a protracted exposure (Langholz et al 1999). The present approach permits fitting of these types of background stratified Poisson regression models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, we noted that ionizing radiation can act as a promoter as well as an initiator of cancer (Doll 1978); that high doses can suppress immune function, which is associated with the appearance of secondary tumors within 2 years of radiotherapy (Appelbaum 1993); and that latencies of less than 5 years have been observed for miners exposed to radon (Hornung and Meinhardt 1987). A recent study of lung cancer among uranium miners found the best estimate of minimum latency to be less than 1 year (Langholz et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…13-15 Although radon exposure has been estimated for all miners in this cohort, we consider a hypothetical situation in which the only radon exposure-related information available on cohort members are the dates of start and end of mining.…”
Section: Introductionmentioning
confidence: 99%